2019
DOI: 10.1016/j.ijdevneu.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sevoflurane exposures during pregnancy inhibit neuronal migration by upregulating prostaglandin D2 synthase

Abstract: Background The second trimester is a period of neurogenesis and neuronal migration, which may be affected by exposure to anesthetics. Studies have suggested that multiple anesthetic exposures may have a significant impact on neuronal migration. Methods Pregnant C57BL/6 mice at embryonic day 14.5 were randomly divided into four groups: Con x 1, Sev x 1, Con x 2, and Sev x 2. Cortical neuronal migration in offspring mice was detected by GFP immunostaining, and the number of cells in the cortex was analyzed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Ptgds was known as a prostaglandin D synthase in brain that catalyzed the conversion of prostaglandin H2 to prostaglandin D2, which acted as a neuromodulator and/or trophic factor in the central nervous system ( 54 ). A previous study reported that multiple exposures of sevoflurane-induced neuronal migration deficit in embryonic neocortex were due to the elevated Ptgds expression level ( 55 ), which also supported our results to a certain extent. Here, we preliminarily identified the role of Ptgds in regulating NSC/IPC migration.…”
Section: Discussionsupporting
confidence: 92%
“…Ptgds was known as a prostaglandin D synthase in brain that catalyzed the conversion of prostaglandin H2 to prostaglandin D2, which acted as a neuromodulator and/or trophic factor in the central nervous system ( 54 ). A previous study reported that multiple exposures of sevoflurane-induced neuronal migration deficit in embryonic neocortex were due to the elevated Ptgds expression level ( 55 ), which also supported our results to a certain extent. Here, we preliminarily identified the role of Ptgds in regulating NSC/IPC migration.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to its traditionally accepted protective effect by decreasing neuronal death and promoting long-term memory consolidation 26 , an appropriate dose of SPC may facilitate endogenous hippocampal neural network reconstruction through neurogenesis and promotion of migration of astrocytes and microglia to the infarcted region for neurocognitive repairment 27,28 . Moreover, Chai reported that multiple use and overdose of sevoflurane in the pregnant period may directly inhibit neural migration in the cortex of offspring 29 . In our present study, we first investigated DG neuron migration and neuron organization after HIE.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have shown completely different subsets of genes to be altered following anesthetic exposure [33,34,[36][37][38][39][40]. However, in these studies, neither the developmental stages nor the exposure conditions were considered for a fair comparison [33,34,[36][37][38][39][40], thus making these findings inconclusive. Other studies using different anesthetics such as isoflurane [41][42][43][44], propofol [34,43] or ketamine [43,45] have also failed to provide a consensus for specific genes altered by anesthetic exposure, as neither the models used nor the experimental conditions were kept consistent.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, two different studies have claimed that early exposure to sevoflurane in rats, either once [31] or three times [32], results in the downregulation of Krüppel-like factor 4 (Kfl4), a transcription factor involved in cell growth, proliferation, or differentiation [35], over both a shorter [31] and a longer term [32]. In contrast, other studies have shown completely different subsets of genes to be altered following anesthetic exposure [33,34,[36][37][38][39][40]. However, in these studies, neither the developmental stages nor the exposure conditions were considered for a fair comparison [33,34,[36][37][38][39][40], thus making these findings inconclusive.…”
Section: Introductionmentioning
confidence: 99%